Superior vena cava syndrome caused by epitheloid hemangioma - Ilić Radoje; Trifunović Zoran; Mandarić Vladimir; Tišma Svetislav (Vojnosanitetski Pregled)
Aim. A case is presented of the surgical treatment of epitheloid hemangioma as a rare cause of superior vena cava syndrome. Case report. A 53-year old woman was admitted to the clinic with the symptoms and signs of superior vena cava syndrome. After clinical evaluation and diagnostic tests, she was operated on through median sternotomy, and the desobliteration of the superior vena cava through longitudinal ca votomy was done. After the desobliteration by the removal of benign tumor from its cavity, vena cava was reconstructed with the continuous prolen suture. Pathohistologicaly, there was the evidence of epitheloid hemangioma that made the subtotal obliteration of the vena cava superior by its expansive growing at the entry in the right atrium. Postoperatively, there was a complete disappearance of the symptoms and signs of superior vena cava syndrome. After an uneventful recovery, the patient was discharged from the hospital.